Substitution Media by Utilizing Banana Peel for In Vitro Culture of Chrysanthemum morifolium - Etty Handayani; Innaka Ageng Rineksane; Supriyatin Kartika Sari; Fany Permatasari (Akademi Komunitas Perkebunan Yogyakarta, 2026)
The use of organic matter in the in vitro culture medium can reduce costs for micropropagation and multiplication of Chrysanthemum in mass production. This study aims to examine the use of banana peel waste in the in vitro culture of Chrysanthemum. The research used an experimental method with single factor and eight treatments with 3 samples and 3 replications. The treatments were: (1) MS medium + BAP 1 ppm + NAA 0.5 ppm, (2) Foliar fertilizer 3 g/L + coconut water 150 mL/L, (3) banana endocarp puree 50 g/L, (4) banana endocarp puree 100 g/L, (5) banana exocarp puree 50 g/L, (6) banana exocarp puree 100 g/L, (7) banana peel puree 100 g/L, and (8) banana peel puree 100 g/L. All banana peel puree treatments were combined with foliar fertilizer 3g/L + coconut water 150 mL/L. The explant used a single nodus of Chrysanthemum with one leaf resulting from the previous in vitro culture. This study used Chrysanthemum varieties Naweswari and Tadasita from Ornamental Plants Research Center, West Java, Indonesia. The results showed that foliar fertilizer medium added by banana peel puree and coconut water has the good potential to be used as a substitution medium in the in vitro culture of Chrysanthemum varieties Naweswari and Tadasita. The banana peel puree 50 g/L in the foliar fertilizer medium shows the best growth in Chrysanthemum in vitro culture in both Naweswari and Tadasita varieties.